Determination of Phytotechnological Parameters of the Dense Extract from Peach (Persica vulgaris) Leaves - E. I. Molokhova; L. V. Ivantsova; V. D. Belonogova (Разработка и регистрация лекарственных средств)
Introduction. Leaves of peach (Persica vulgaris), containing a large amount of biologically active substances, including flavonoids, are considered as promising plant source for producing extraction preparations.Aim. The purpose of the study: to establish the influence of phytotechnological parameters for efficiency of isolation of complex of biologically active substances from peach leaves.Materials and methods. The object of the study was samples of dried leaves of the cultivated peach tree – Persica vulgaris Mill. (Rosaceae family) collected during the growing season (at the end of August). The main technological parameters of vegetable raw materials were studied: average particle size and fractional composition, volume characteristics of specific, volume and bulk mass, porosity, porosity and free volume of the raw material layer, аs well as the absorption coefficient of the extractant.Results and discussion. The obtained values of the fractional composition and volume characteristics indicate the expediency of using the maceration method in plant raw materials extraction. Experimental studies were carried out to select optimal modes of extraction of flavonoids from peach leaves (extractant, extraction temperature, extraction duration, degree of raw material grinding, hydromodule), which ensure high output of BAS complex into extract.Conclusion. The study presents the analysis of phytotechnological parameters of peach leaves, a rational extraction method is justified – maceration at heating with periodic stirring, and extraction conditions are determined; providing maximum yield of active substances: temperature – 70 °С in 40 min, extractant – alcohol, ethyl solution 70 %, degree of raw material grinding – 2 mm, raw material : extractant ratio (1 : 10).